Analisis Nilai-Nilai Karakter pada Peristiwa Pemberontakan Trunajaya Tahun 1674-1679 - Zilfi Khuzaimah; Yeni Asmara; Isbandiyah Isbandiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the character values ​​of the Trunajaya rebellion in 1674-1679. The method used in this research is library research or descriptive qualitative with a historical approach related to research. The results show that the character values ​​contained in the Trunajaya rebellion in 1674-1679 can be used as examples and lessons for all of us, especially the younger generation, so that they can be applied in everyday life. Because the progress of a nation not only has abundant natural resources but also has human resources of good character. The conclusion of the study is that the character values ​​that can be imitated in the Trunajaya rebellion in 1674-1679 include: The character value of patriotism, the character value of the national spirit, the value of social care character, the value of hard work character and the value of religious character. Keywords: Character, Value, Trunajaya